2022
DOI: 10.1007/s00127-021-02208-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychopathology in Children and Adolescents in Lebanon Study (PALS): a national household survey

Abstract: Introduction Psychiatric disorders are among the leading causes of disability in children and adolescents globally. In Lebanon, a country that has endured a prolonged history of conflict and economic and political uncertainty, mental health surveys in children and adolescents have been limited to specific disorders or specific settings or cities. PALS (Psychopathology in Children and Adolescents in Lebanon Study) is the first study to screen a nationally representative sample of children and adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In Lebanon, according to one study 10 , just 5% of children with depression sought professional treatment.…”
Section: A Depressing Trendmentioning
confidence: 99%
“…In Lebanon, according to one study 10 , just 5% of children with depression sought professional treatment.…”
Section: A Depressing Trendmentioning
confidence: 99%
“…This highlights the existence of a wide gap between mental health needs and mental health help seeking in children. In a more recent study examining probable disorders in children and adolescents following the Beirut port explosion, the findings reported high rates for anxiety (64%), PTSD (52%), and depression (33%), yet 61.5% did not seek help (Maalouf, Alrojolah, et al, 2022;Maalouf, Haidar et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…The prior puts them at greater risk for developing mental health problems which raises the need for school psychology services. A national household study conducted between February 2018 and November 2018 investigated psychopathology in a sample of 1517 children and of adolescents in Lebanon, and found that, while 33% of the sample displayed at least one psychiatric disorder, only 5% sought professional help (Maalouf, Alrojolah, et al, 2022; Maalouf, Haidar et al, 2022). This highlights the existence of a wide gap between mental health needs and mental health help seeking in children.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a review of multiple studies suggests a global prevalence of about 6.5% for anxiety disorders in children. 4 In Lebanon, a study published in 2022 about mental health issues, in adolescents and children, found that 32.7% of children have a psychiatric disorder, but only 5% were professionally managed 5 .…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, anxiety is more common in girls (27.41%) than boys (15.6%), and in children aged above 12 years old . 5 Studies showed that most of the clinical presentations involving anxiety are exhibited by physical symptoms. 6,7 Children with anxiety presents somatic symptoms, the most observed ones include restlessness, abdominal pain, palpitations, along with sweating and trembling.…”
Section: Introductionmentioning
confidence: 99%